2015
DOI: 10.3109/21681805.2015.1005664
|View full text |Cite
|
Sign up to set email alerts
|

Parastomal hernia after ileal conduit with a prophylactic mesh: a 10 year consecutive case series

Abstract: The prevalence of PSH after ileal conduit with a prophylactic mesh corresponded to that of colostomies with a prophylactic mesh. A prophylactic mesh did not seem to be associated with complications. The degree to which a prophylactic mesh may reduce the rate of PSH after an ileal conduit should be established in randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Overall, 38 potentially relevant studies were identified, of which 28 were excluded because they were not RCTs ( Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 38 potentially relevant studies were identified, of which 28 were excluded because they were not RCTs ( Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…At a median follow-up of 35 months, they reported a clinical PH rate of 14% and no mesh-related complications. 11 …”
Section: Prophylactic Mesh After Open Radical Cystectomymentioning
confidence: 99%
“…7-10 There have been no randomized, controlled trials of mesh placement in patients undergoing urinary diversion and published experience is limited to single institution series of select patients. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Nonrandomized series of consecutive patients receiving prophylactic mesh at the time of index surgery have recently been published. Styrke et al [ 47 ] reported a single institution, 10-year consecutive series of 114 patients having prophylactic mesh placed in the sublay position at the time of RC and IC formation. After a median follow-up of 35 months, they reported a cPH rate of 14% in 58 evaluable patients and no mesh-related complications.…”
Section: Mesh Placement At Index Surgery To Prevent Parastomal Herniamentioning
confidence: 99%